Current density limitation during disruptions due to plasma-sheaths. (1st August 2022) - Adamek, J.; Artola, F.J.; Loarte, A.; Matveeva, E.; Cavalier, J.; Pitts, R.A.; Roccella, R.; Lehnen, M.; Havlicek, J.; Hron, M.; Panek, R.; Team, the COMPASS
Abstract: The presented experimental study realized in the COMPASS tokamak demonstrates, for the first time, that the current density that flows from the plasma into the vacuum vessel during disruptions is limited by the ion particle flux. Such a limitation shows that, at least in COMPASS, the sheath that forms between the plasma and the first wall dominates the halo current flow. This observation is achieved by measuring simultaneously the ion saturation current with negatively biased Langmuir probes and the halo current with grounded probes to the vacuum vessel. These comparative measurements, which were never performed during disruptions in other machines, directly confirm that the halo current density remains below the ion particle flux in COMPASS. The study also shows, using Mirnov coils measurement, that the total electric current entering the wall grows with the plasma current while the current density obtained by Langmuir probes remains unaffected. This, together with the current density limitation, leads to a novel finding that the halo current width increases with the pre-disruptive plasma current, which limits the local forces. The new findings reported here could also provide potential constraints on the modeling of disruption-induced loads on future reactor scale tokamaks and motivation for further experiments on existing devices.